Acetylene and Ethylene: Universal C2 Molecular Units in Cycloaddition Reactions - Ledovskaya, Maria S.; Voronin, Vladimir V.; Rodygin, Konstantin S.; Ananikov, Valentine P. (Synthesis, 2021)
Acetylene and ethylene are the smallest molecules that contain an unsaturated carbon–carbon bond and can be efficiently utilized in a large variety of cycloaddition reactions. In this review, we summarize the application of these C2 molecular units in cycloaddition chemistry and highlight their amazing synthetic opportunities.1 Introduction2 Fundamental Features and Differences of Cycloaddition Reactions Involving Acetylene and Ethylene3 (2+1) Cycloaddition4 [2+2] Cycloaddition5 (3+2) Cycloaddition6 [4+2] Cycloaddition7 (2+2+1) Cycloaddition8 [2+2+2] Cycloaddition9 The Use of Acetylene and Ethylene Cycloaddition for Deuterium and 13C Labeling10 Conclusions
Keywords: acetylene; cyclizations; cycloaddition reaction; ethylene; heterocyclic compounds; organic synthesis